Endoluminal Ultrasound of Neoduodenum Following Pancreas-Preserving Total Duodenectomy for Familial Adenomatous Polyposis - Beamish, Andrew J; Roberts, S Ashley; Ansell, James; Al-Sarireh, Bilal (JOP. Journal of the Pancreas, 2012)
<!–[if gte mso 9]> 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 14 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> <span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: Calibri; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Familial adenomatous polyposis affects around 2-10 per 100,000 population. Untreated, it inevitably leads to colon cancer. Prophylactic panproctocolectomy has led to improved survival. The resulting extension to follow-up has revealed that 70-100% of patients with familial adenomatous polyposis go on to develop duodenal polyposis and the lifetime risk of duodenal carcinoma in this group is up to 10%. Treatment for those not locally resectable requires pancreaticoduodenectomy. In recent years, pancreas-preserving total duodenectomy has emerged as a safe alternative to pancreaticoduodenectomy. Endoscopy has previously been safely performed in patients following pancreas-preserving total duodenectomy. Case report We report successful endoscopic ultrasound (EUS) assessment and trans-neoduodenal EUS-guided fine needle aspiration biopsy (EUS-FNA) of the pancreas and adjacent tissue in a 45-year-old man with familial adenomatous polyposis who has previously undergone pancreas-preserving total duodenectomy. EUS confirmed the mass was most likely to represent a metastasis in a local lymph node. EUS-FNA confirmed invasive malignancy. A Kausch-Whipple pancreaticoduodenectomy was performed successfully and post-operative recovery has been excellent. Conclusion The authors consider this to be the first report of successful EUS and EUS-FNA performed through the neoduodenum fashioned during pancreas-preserving total duodenectomy.